Rome enters the Greek East from anarchy to hierarchy in the Hellenistic Mediterranean, 230-170 BC - Eckstein, Arthur M. (Wiley-Blackwell, 2012)
This volume examines the period from Rome's earliest involvement in the eastern Mediterranean to the establishment of Roman geopolitical dominance over all the Greek states from the Adriatic Sea to Syria by the 180s BC.